Effect of radiofrequency Catheter ablation on the left ventricular Ejection fraction in Patients with long-Standing Persistent atrial fibrillation - Suslina, Y.; Rudenko, N.; Doronin, A.; Meshkova, M. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Introduction. Atrial fibrillation (AF) and chronic heart failure (CHF) have common risk factors, pathophysiological mechanisms, and often are concomitant diseases. Two meta-analyses of randomized clinical trials showed the effectiveness of AF ablation in patients with CHF, including those with long-standing persistent AF. The objective of this study is to analyze the effect of radiofrequency catheter ablation (RFA) on the increase of the left ventricular ejection fraction (LVEF) in patients with long-standing persistent AF on the basis of our own data. Materials and methods. This article describes the authors’ own experience of RFA in 57 consecutive patients with long-standing persistent AF who underwent 67 ablations. In 20 (35.08%) patients, LVEF was less than 50%. The patients were divided into 2 groups: group 1 included patients with low LVEF (< 40%), and group 2 included those with mid-range LFEV (40–49%). We analyzed the LVEF increase. Results and discussion. During the observation period of 9.2 ± 3.4 (6–12) months, sinus rhythm after the last procedure was preserved in 15 (75.0%) patients. The average LVEF increase was 15.8 ± 3.22% in group 1 and 9.3 ± 2.6% in group 2. Conclusion. Thus, catheter ablation has positive effect on LVEF in patients with long-standing persistent AF.